Severe convective storms and tornadoes : observations and dynamics - Bluestein, Howard B. (Springer Praxis Books, 2013)
This book is a focussed, comprehensive reference on recent research on severe convective storms and tornadoes. It will contain many illustrations of severe storm phenomena from mobile Doppler radars, operational Doppler radars, photographs and numerical simulations.